Leverage and Firm Value: How Capital Structure Impacts Valuation on Finnish Public Firms - Rantasalo, Ramses (My University, 2025)
The impact of capital structure on firm value is a central question in corporate finance. The thesis frames the question through competing theories, such as Modigliani and Miller, trade-off theory, pecking order theory, agency theory, and market timing theory, and observes that the existing empirical evidence is mixed across countries and settings. Finland is used as the empirical setting due to its distinct market characteristics and the limited existing evidence on the relationship between leverage and firm value for Finnish listed firms. The main research question asks how capital structure affects the valuation of Finnish public companies listed on Nasdaq Helsinki, with two sub-questions on how leverage ratios affect Tobin’s Q and how the results compare with international evidence and theory predictions. The empirical analysis uses a two-way fixed effects panel regression with firm and year effects and firm-clustered standard errors, with Tobin’s Q as the dependent variable and size, profitability, and price-to-book included as controls. The data sample covers Finnish non-financial firms over fiscal years 2015-2025 using LSEG Workspace data extracted on 9 October 2025, with 1705 firm-year observations and 1460 in the core models after 1st/99th winsorisation and dropping missing fields. The model is estimated separately across six alternative leverage definitions. Across leverage definitions, the thesis reports a negative within-firm relationship between leverage and Tobin’s Q, with the clearest statistical support for the equity-scaled leverage measures, while the asset-scaled measures share the same sign but have weaker statistical support. The results offer no support for an inverted-U pattern consistent with trade-off theory. It is observed that leverage is more damaging to firm value when price-to-book, used as a growth proxy, is high.

Pääomarakenteen vaikutus yrityksen arvoon on keskeinen kysymys yritysrahoituksessa. Tässä tutkielmassa kysymystä tarkastellaan kilpailevien teorioiden näkökulmista. Teoreettinen viitekehys sisältää Modiglianin ja Millerin mallin, kompromissiteorian (trade-off-teorian), nokkimisjärjestysteorian, agenttiteorian sekä markkinoiden ajastusteorian. Aiempi empiirinen näyttö on vaihtelevaa eri maissa ja tutkimusasetelmissa. Suomi valitaan tutkimuskohteeksi sen markkinoiden erityispiirteiden sekä suomalaisia listattuja yhtiöitä käsittelevän rajallisen aiemman tutkimuksen vuoksi. Päätutkimuskysymys tarkastelee, miten pääomarakenne vaikuttaa Nasdaq Helsingissä listattujen suomalaisten pörssiyhtiöiden arvostukseen. Alakysymykset käsittelevät sitä, miten velkaantuneisuuden mittarit vaikuttavat Tobinin Q:hun ja miten tulokset suhteutuvat kansainväliseen näyttöön ja teorioiden ennusteisiin. Empiirisessä osiossa estimoidaan kaksisuuntainen kiinteiden vaikutusten paneeliregressio, jossa huomioidaan yritys- ja vuosivaikutukset sekä yritystasolla klusteroidut keskivirheet. Selitettävä muuttuja on Tobinin Q, ja kontrollimuuttujina käytetään yrityksen kokoa, kannattavuutta ja hinta-kirjanpitoarvo-suhdetta (P/B). Aineisto kattaa suomalaiset ei-finanssialan yhtiöt tilikausilta 2015–2025. LSEG Workspace- aineisto on poimittu 9.10.2025. Havaintoja on 1705 yritysvuotta ja keskeisimmissä malleissa 1460 havaintoa 1./99. prosenttipisteiden winsoroinnin ja puuttuvien havaintojen poistamisen jälkeen. Malli estimoidaan erikseen kuudella vaihtoehtoisella velkaantuneisuuden määritelmällä. Tulokset osoittavat velkaantuneisuuden ja Tobinin Q:n välille negatiivisen yhteyden yrityksen sisällä. Tilastollinen näyttö on vahvinta oman pääoman avulla skaalatuissa velkaantuneisuusmittareissa, kun taas taseen loppusummalla skaalatuissa mittareissa yhteyden etumerkki on sama, mutta tilastollinen merkitsevyys on heikompaa. Tulokset eivät tue kompromissiteorian mukaista käänteistä U-muotoa velkaantuneisuuden ja yritysarvon välillä. Velkaantuneisuuden haitallisen yhteyden yritysarvoon havaitaan korostuvan, kun P/B, jota käytetään kasvun sijaismuuttujana, on korkea.
Keywords: Capital structure, leverage, firm value, Tobin’s Q, debt-to-equity ratio, panel regression, pääomarakenne, velkaantuneisuus, yrityksen arvo, Tobinin Q, velkaantuneisuusaste (D/E), paneeliregressio